2011
DOI: 10.1111/j.1467-6435.2011.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Welfare Cost of Forest Fires: a Life Satisfaction Approach

Abstract: Kountouris, Y., Remoundou, K. (2011). Valuing the Welfare Cost of Forest Fires: a Life Satisfaction Approach. Kyklos, 64 (4), 556-578.Sustainable natural resource management is at the core of the policy agenda, given the wide array of goods and services environmental resources generate, that significantly contribute to social welfare and productive capacity of modern economies. Likewise, there is a large policy interest in the monetization of the economic effects of environmental damages, to enable the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…To illustrate the economic importance, studies in this field often provide a transformation of non-monetary effects into equivalent monetary figures (e.g., Carroll et al 2009;Luechinger 2009;Luechinger and Raschky 2009;Kountouris and Remoundou 2011). 4 While the study here is also motivated by the idea that subjective well-being is generally translatable and measurable in economic terms, the prime motivation comes from a different and more political viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the economic importance, studies in this field often provide a transformation of non-monetary effects into equivalent monetary figures (e.g., Carroll et al 2009;Luechinger 2009;Luechinger and Raschky 2009;Kountouris and Remoundou 2011). 4 While the study here is also motivated by the idea that subjective well-being is generally translatable and measurable in economic terms, the prime motivation comes from a different and more political viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of a well-known disaster of Hurricane Katrina, as far as we know, there have been no studies that provide monetary estimates of psychological suffering, and only a few studies such as Kimball et al (2006), Rateau (2009), Rhodes (2010), andLaJoie et al (2010) have addressed well-being after the disaster. Luechinger and Raschky (2009) and Kountouris and Remoundou (2011) are the scarce examples of monetary evaluations of psychological suffering from natural disasters through the experienced utility approach. These works, however, were not based on an acute and unprecedented single event as in the case of our study.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies report negative effects on the population in the respective country or area (Carroll, Frijters, & Shields, 2009;Kimball et al, 2006;Kountouris & Remoundou, 2011;Luechinger & Raschky, 2009). Recent studies have also found that distantly remote disasters can have negative effects on populations in other countries (Metcalfe et al, 2011), even when a similar disaster seems geographically impossible in that country (Goebel, Krekel, Tiefenbach, & Ziebarth, 2015).…”
Section: Literature and Hypothesesmentioning
confidence: 94%